Non-specific markers of inflammation in bare-nosed wombats (Vombatus ursinus) with sarcoptic mange - Wilkinson, Vicky; Richards, Shane A.; Carver, Scott; Næsborg-Nielsen, Christina; Cray, Carolyn; Rossi, Gabriele (Frontiers in Veterinary Science, 2024)
Sarcoptic mange, caused by epidermal infection with Sarcoptes scabiei, negatively impacts the health, welfare, and local abundance of bare-nosed wombats (Vombatus ursinus) in Australia. Improved understanding of the host immune response to disease and its contribution to pathophysiology could be used to inform management actions for this species in and ex situ. To evaluate the immune response of bare-nosed wombats to sarcoptic mange, we validated three assays (haptoglobin, agarose gel electrophoresis, and micro-erythrocyte sedimentation rate) measuring non-specific markers of inflammation using serum samples from free-living wombats from Tasmania (n=33). We then analysed correlations between the assay results for each non-specific marker of inflammation and wombat’s sarcoptic mange scores, and performed histopathological examinations to investigate association of the acute phase response with systemic amyloidosis. We present evidence that haptoglobin and erythrocyte sedimentation rate increased, and albumin decreased, in association with sarcoptic mange scores. This research demonstrates links between the acute phase response and sarcoptic mange severity in bare-nosed wombats, highlighting the utility of non-specific markers of inflammation for aiding assessment of the systemic effects of mange. Showing the value of agarose gel electrophoresis, we also identified specific acute phase proteins warranting future evaluation and found evidence of an immunoglobulin response in mange-affected wombats, revealed by increasing -globulins in association with apparent disease severity. Meanwhile, owing to its relatively low resource requirements and rapidity, the erythrocyte sedimentation rate assay may be useful as a point-of-care test to support therapeutic decisions in the field. Our methods and findings are likely to be applicable to a range of other clinical and population health scenarios in captive and free-living wombats, and species impacted by sarcoptic mange globally.